Polyvinylidene Fluoride/Reduced Graphene Oxide Layers on SiOxNy/Poly(ethylene terephthalate) Films as Transparent Coatings for Organic Electronic Devices and Packaging Materials - Kim, Seo Gyun; You, Nam-Ho; Ku, Bon-Cheol; Lee, Heon Sang (AMER CHEMICAL SOC, 2020)
Transparent, high gas barrier films are crucial in the medical, food, and electronic industries. The main properties required for electronic devices such as flexible displays include transmittance of >90% and oxygen transmission rates (OTRs) and water vapor transmission rates (WVTRs) of 10(-3) to 10(-6) cc(g) m(-2) day(-1). Herein, we report reduced graphene oxide (rGO)/inorganic and organic/inorganic composites coated on poly(ethylene terephthalate) (PET) film with superior oxygen and water vapor barrier properties and high transmittance. The OTR (at 23 degrees C, 0% relative humidity) and WVTR (at 37.8 degrees C, 100% relative humidity) values of the composite films (140 mu m) decreased by 8 x 10(4) times and 6.71 x 10(2) times, respectively, relative to those of the PET substrate film (125 mu m). The transmittance of the composite films at 550 nm was 84%, corresponding to only a 9% decrease compared to that of the PET film. Additionally, with only nanolayers of SiOxNy (100 nm) and rGO (13 nm) coating on the PET substrate, the OTR and WVTR were reduced by 2000 times and 470 times, respectively. A polyvinylidene fluoride/rGO (PVDF/rGO) layer on the SiOxNy/PET substrate showed 8.8 x 10(5) times lower oxygen permeability and 1.6 x 10(4) times lower water permeability compared to those of PVDF/rGO on the PET substrate, implying that the inorganic SiOxNy nanolayer is crucial, affording a synergistic effect toward the barrier film. The gas permeabilities of the composite films strongly depend on the design of the coating structure, rGO content, and blend ratio of PVDF and PMMA; this allows efficient control of the nanodefects of the composite film. This study shows the significance of inorganic materials and the synergistic effect of composites on barrier films, which are required for applications in organic electronic devices and packaging materials.
Keywords: GAS BARRIER PROPERTIES; THIN-FILMS; WATER-VAPOR; PERMEATION; ENCAPSULATION; MECHANISMS; NANOSHEETS; SIOXNY; AL2O3